2019
DOI: 10.1016/j.eats.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

How to Succeed in Arthroscopic Anterior Cruciate Ligament Primary Repair? Step-by-Step Technique

Abstract: Historically, poor results of open primary repair of anterior cruciate ligament (ACL) injuries have been reported. It has recently been recognized that favorable outcomes of primary ACL repair are possible when selectively performed in patients with proximal tears and good tissue quality. Moreover, with arthroscopic technological advances, primary repair can be a valuable treatment option for patients with proximal tears. Preserving the native ACL has several advantages, including maintenance of native proprio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Descriptions of suture configurations in preparing the ACL remnant in repairs are varied in the literature. 11 , 25 Evidence to support one method over another remains anecdotal at this point. Comparison of the strength of locking sutures can be found in the flexor tendon literature, which has shown that the number of suture strands crossing the repair site is more important than the suture configuration itself.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptions of suture configurations in preparing the ACL remnant in repairs are varied in the literature. 11 , 25 Evidence to support one method over another remains anecdotal at this point. Comparison of the strength of locking sutures can be found in the flexor tendon literature, which has shown that the number of suture strands crossing the repair site is more important than the suture configuration itself.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Suture bridge technique has shown good results for fixation of ACL tibial avulsions. [6][7][8] Post-operative arthrofibrosis being most common complication encountered after suture bridge fixation. Delayed mobilization or mechanical impingement can lead to this complication.…”
Section: Discussionmentioning
confidence: 99%
“…2 FiberWire ® and TigerWire ® stitches (Arthrex) that were looped through the ligament using a lasso-loop knot-tying configuration (Fig. 1 a) [ 16 ]. The stitches were passed through the anteromedial and posterolateral bundle of the ACL.…”
Section: Methodsmentioning
confidence: 99%
“…Most articles recommend surgery within 4 weeks from injury; however, there is a wide variety of delay until treatment, including at least one case report of a patient treated 11 years after injury [ 14 ]. Since the renewal of interest in ACL primary repair has only been recent, there has been little investigation regarding MRI evaluation after ACL primary repair [ 7 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%